PENGEMBANGAN OBJEK WISATA ALAM SEBAGAI DAERAH TUJUAN WISATA DI DAERAH PERBATASAN - Veneranda Rini Hapsari; Usman Usman; Rissa Ayustia (Politeknik Negeri Ambon, 2020)
The development of tourist objects is a common problem in an area that has tourist objects, because if the development is well managed, it will have a positive impact on all parties. If there is a development of a tourist attraction, it will indirectly create business opportunities and increase income in the community. The purpose of this research is to find out and get the results from tourism villages, and from developing tourist objects into tourist villages can expand business opportunities. This study uses a qualitative method. The sampling technique was purposive sampling, data collection techniques used observation, interviews and documentation.The results showed that the development of tourist villages can be seen from the increasing number of tourist visits in Setanga Lestari as well as the characteristics of tourist villages that are the main attraction of developing tourist objects. The participation of the local community can be seen from the support of the community who participated in the development of the tourist village. With this tourism village, it can open business opportunities and increase the income of the people in the area.